2022
DOI: 10.1093/jhps/hnac008
|View full text |Cite
|
Sign up to set email alerts
|

Adding false-profile radiographs improves detection of developmental dysplasia of the hip, data from the CHECK cohort

Abstract: The aim of this study was to determine the additional value of the false-profile (FP) view radiograph in the diagnosis of developmental dysplasia of the hip (DDH), as compared with an anteroposterior (AP) pelvic radiograph only, and evaluate the correlation between the Wiberg-lateral center edge angle (W-LCEA) and Wiberg-anterior center edge angle (W-ACEA). We used baseline data from a nationwide prospective cohort study (Cohort Hip and Cohort Knee). DDH was quantified on AP pelvic and FP hip radiographs using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Based on their different characteristics, ACEA FP could be more suitable for determining anterior hip stability [ 18–20 ] because ACEA FP was taken in a standing position. That is the position in which the patient’s hip joint is actually performing its weight-bearing function [ 21 ]. While ACEA CT describes the morphology of the anterior hip joint more precisely, it is more suitable for evaluating the potential impingement which may occur after hip reorientation [ 19 , 22–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their different characteristics, ACEA FP could be more suitable for determining anterior hip stability [ 18–20 ] because ACEA FP was taken in a standing position. That is the position in which the patient’s hip joint is actually performing its weight-bearing function [ 21 ]. While ACEA CT describes the morphology of the anterior hip joint more precisely, it is more suitable for evaluating the potential impingement which may occur after hip reorientation [ 19 , 22–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,22 A recent multicenter prospective cohort study suggested that obtaining a false-profile radiograph adds strong value to the diagnosis of hip dysplasia in the young adult in cases that would otherwise remain missed with a single anteroposterior view. 12 However, Herfkens et al 12 have emphasized that the Lequesne view is often unsuitable because of superimposition of osseous structures caused by alterations in tilt and rotation (of both the acetabulum and the femur), which cannot be adjusted for as in an anteroposterior view. Different studies have used ACEA to understand outcomes and prognosis after surgical treatment of femoroacetabular impingement and hip dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Next, a vertical line is drawn perpendicular to a horizontal reference line connecting both femoral heads (Figure 2). The LCEA is the angle between the vertical line and a line drawn from the center of the femoral head to the lateral acetabular rim 32,33 . The ACEA is constructed from the FP radiograph in a similar way, except that the vertical line is drawn perpendicular to the horizontal line of the radiographic film (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…The LCEA is the angle between the vertical line and a line drawn from the center of the femoral head to the lateral acetabular rim. 32,33 The ACEA is constructed from the FP radiograph in a similar way, except that the vertical line is drawn perpendicular to the horizontal line of the radiographic film (Figure 3). 29,34 Pincer morphology was defined as LCEA ≥ 40 , ACEA ≥ 40 , or both the ACEA and LCEA ≥ 40 .…”
Section: Significance and Innovationsmentioning
confidence: 99%